Finding the best examples of healthcare quality improvement in Sub-Saharan Africa. Issue 5 (25th October 2010) - Liu, Constance; Babigumira, Joseph; Chiunda, Allan; Katamba, Achilles; Litvak, Ilya; Miller, Lakisha; Namagembe, Imelda; Sekandi, Juliet; Seicean, Andrea; Seicean, Sinziana; Neuhauser, Duncan
Abstract : Background: The purpose of this study was to summarise the current state of healthcare quality improvement literature focusing on sub-Saharan Africa. Methods: Conventional methods of searching the literature were quickly found to be inadequate or inappropriate, given the different needs of practitioners in sub-Saharan Africa, and the inaccessibility of the literature. Results: The group derived a core list of what were deemed exemplary quality improvement articles, based on consensus and a search into the "grey" literature of quality improvement. Conclusions: Quality improvment articles from sub-Saharan Africa are difficult to find, and suffer from a lack of centrality and organisation of literature. Efforts to address this are critical to fostering the growth of quality improvement literature in developing country settings.